2022
DOI: 10.3390/cancers14246111
|View full text |Cite
|
Sign up to set email alerts
|

Sodium New Houttuyfonate Inhibits Cancer-Promoting Fusobacterium nucleatum (Fn) to Reduce Colorectal Cancer Progression

Abstract: Colorectal cancer (CRC) is a major cause of morbidity and mortality worldwide. Recent studies showed that the common anaerobe Fusobacterium nucleatum (Fn) is closely associated with a higher risk for carcinogenesis, metastasis, and chemoresistance of CRC. However, there is no specific antimicrobial therapy for CRC treatment. Herbal medicine has a long history of treating diseases with remarkable effects and is attracting extensive attention. In this study, we tested six common phytochemicals for their antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…C-BAs interact with intestinal barrier cells including intestinal epithelial cells and the endothelium and disrupt this fundamental barrier, which can lead to the systemic entry of harmful entities, such as intestinal microbes and their metabolites, and initiation of tumor-promoting inflammation. 43 , 48 We demonstrated the effect of individual C-BAs in damaging the vascular barrier in HUVECs and found that GCDCA was the most potent BA in permeabilizing the HUVEC monolayer barrier, followed by TCA and TCDCA, with the least effects seen for GCA. DCHD treatment reversed HUVEC barrier disruption induced by GCDCA and increased the expression of TJ proteins.…”
Section: Discussionmentioning
confidence: 94%
“…C-BAs interact with intestinal barrier cells including intestinal epithelial cells and the endothelium and disrupt this fundamental barrier, which can lead to the systemic entry of harmful entities, such as intestinal microbes and their metabolites, and initiation of tumor-promoting inflammation. 43 , 48 We demonstrated the effect of individual C-BAs in damaging the vascular barrier in HUVECs and found that GCDCA was the most potent BA in permeabilizing the HUVEC monolayer barrier, followed by TCA and TCDCA, with the least effects seen for GCA. DCHD treatment reversed HUVEC barrier disruption induced by GCDCA and increased the expression of TJ proteins.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that CEACAM1 and TIGIT inhibitors can be used as potential adjuvant drugs for CRC [17] . At present, some small molecule drugs under clinical trial are screened, such as azelnidipine and liothyronine [18] . A recent study has shown that Sodium New Houttuyfonate (SNH) significantly inhibits the progression of CRC by targeting F. nucleatum's membrane-associated protein FadA, leading to FadA polymerization, membrane rupture, and penetration, which blocks the tumor-promoting activity of F. nucleatum and F. nucleatum-associated cancer-driven inflammation, protecting the intestinal barrier [19] .…”
Section: Therapeutic Targetsmentioning
confidence: 99%
“…Based on this finding, Song et al considered neutralizing or modulating LPS produced by gut microbes as a potential treatment for colorectal cancer. Therefore, they suggest that genetically engineered bacteria that secrete LPS traps or PmB produced by Bacillus polymyxa are promising therapeutic approaches to kill Gram-negative bacillus instead of Activating Wnt/β-catenin signaling pathway [14] ; Activating NF-κB signaling pathway and upregulating miR-21 [15] ; Activating MyD88 signaling pathway [16] Small molecule compound inhibitors: Azelnidipine and liothyronine [18] . Sodium New Houttuyfonate (SNH) [18] .…”
Section: Microbiota In Immunotherapy Gram Negative Bacillusmentioning
confidence: 99%
“…nucleatum may promote the progression and metastasis of cancers has spurred research aimed at identifying antivirulence and antimicrobial agents to eradicate F. nucleatum from tumor environments. The advantage of eliminating F. nucleatum was demonstrated in a study by Bullman et al, wherein mice treated with the antimicrobial metronidazole exhibited a decrease in F.…”
Section: Introductionmentioning
confidence: 99%